Intriguing C–H⋯Cu interactions in bis-(phenanthroline)Cu(i) redox mediators for dye-sensitized solar cells. Issue 4 (21st December 2017) - Colombo, Alessia; Ossola, Rachele; Magni, Mirko; Roberto, Dominique; Jacquemin, Denis; Castellano, Carlo; Demartin, Francesco; Dragonetti, Claudia
Abstract : For the first time, an anagostic interaction is found between a H atom of a methyl group and a copper site in the bis-2-tertbutyl(phenanthroline)Cu(i ) complex. Abstract : We have synthesized and characterized a series of bis-(phenanthroline)Cu(i ) complexes of interest as redox mediators for dye-sensitized solar cells. This study led to the discovery of intriguing anagostic interactions between the hydrogen atom and the copper center as evidenced by X-ray diffraction studies on a single crystal. Remarkably, an anagostic interaction was found between a H atom of a methyl group and a copper site.